Transportation Costs and Time Impact of the China-Pakistan Economic Corridor - Muddassar Ashraf; Zheng Shiyuan (International Journal of Regional Development, 2022)
The China-Pakistan Economic Corridor (CPEC), which is part of China’s Belt and Road plan, is a network of infrastructure, commerce, and investment projects, as well as energy and technology projects, now under construction in Pakistan and China’s Western Xinjiang province. The China-Pakistan Economic Corridor (CPEC), which Pakistani officials have labelled as a "game changer," is the most recent manifestation of the two countries’ increasing ties. Because they help to reduce freight prices and transit times, transportation and infrastructure are referred to as major trade levers. This research is primarily concerned with the concept of logistics shipping prices and travel times. China supplies Europe and the Middle East with a reliable, low-cost supply line. The study analyses data in a qualitative and descriptive manner. The study investigates how the CPEC will impact trade in terms of shipping costs and trip time. Transportation and infrastructure are considered critical trade issues since they help to reduce shipping costs and transit times. In order to generate revenues and assure timely product delivery, modern organizations strive to reduce shipping costs and transit times. The goal of this research is to examine the CPEC’s significance and its impact on import and export costs as well as transit durations. This study also compares the current path to the suggested itinerary. The study takes a qualitative and descriptive approach to its investigation. The study’s starting point was the dry port of Kashgar in western China, with three ports in each European and Middle Eastern countries serving as destinations. The three European ports of Hamburg, Le Havre, and Rotterdam, like the selected Middle Eastern ports of Jeddah, Kuwait, and Oman, which meet China’s energy demands, share a considerable trading volume with China. When a 40-foot container is delivered using the current route, the variables time of travel and shipping cost are estimated in the first phase. In the third step, both current and potential CPEC routes are analysed. Because predicting the exact future road transportation cost of CPEC is difficult, the average value of current road transportation costs is used in this analysis. The findings show that shipping costs will be greatly lowered if the proposed CPEC route is implemented. Shipping costs between Kashgar and destination ports can be reduced by 36% for European ports, 50% for Jeddah and Kuwait, and 68 percent for Oman. Furthermore, the transit time from European ports to Jeddah will be reduced by 10-11 days, 15-18 days for Kuwait, and 10 days for Oman.